Commendable Pr3+-activated Ba2Ga2GeO7 phosphor with high-brightness white long-persistent luminescence. Issue 22 (15th May 2019) - Li, Huimin; Pang, Ran; Luo, Yanqing; Wu, Haiyan; Zhang, Su; Jiang, Lihong; Li, Da; Li, Chengyu; Feng, Jing; Zhang, Hongjie
Abstract : Novel white long-persistent phosphor Ba2 Ga2 GeO7 :Pr 3+ was synthesized and characterized by its structural information, photoluminescence and long-persistent luminescence properties. Abstract : Long-persistent phosphors can be used in diverse fields, such as emergency instruction, information storage and in vivo bioimaging. Currently, progress in research and development of white long-persistent phosphors is slow, although there is growing demand for applications in certain conditions. In this work, a novel white long-persistent phosphor Ba2 Ga2 GeO7 :Pr 3+ was synthesized and systematically investigated through its structural information, photoluminescence and phosphorescence properties. Under ultraviolet light excitation, this phosphor gives white emission containing greenish-blue and red components stemming from 3 P0 and 1 D2 multiplet electron transitions in the 4f level of Pr 3+ . The luminescent color of the phosphors is relatively stable at different temperatures and Pr 3+ concentrations. Bright white afterglow can be observed by the naked eye in the dark for 3 hours after removal of the excitation source. Finally, a feasible afterglow mechanism of Ba2 Ga2 GeO7 :Pr 3+ with a trap–detrap scenario was proposed to clarify the generation of the white afterglow.